A detailed investigation of gamma and neutron shielding capabilities of ternary composites doped with polyacrylonitrile and gadolinium (III) sulfate. (June 2023) - Erkoyuncu, İ. and Akman, F. and Ogul, H. and Kaçal, M.R. and Polat, H. and Demirkol, İ. and Dilsiz, K. and Ertuğral, B.
Abstract: The shielding efficiencies of gamma and neutron radiations for ternary composites containing polyester resin, polyacrylonitrile and gadolinium (III) sulfate at different ratios were investigated in the present study. In order to investigate the gamma radiation shielding capacity of the produced ternary composites, linear and mass attenuation coefficients, half value layer, effective atomic number and radiation protection efficiency parameters were determined experimentally, theoretically and using the GEANT4 simulation code. The gamma shielding capabilities of the composites were studied in the photon energy range of 59.5–1332.5 keV. In order to investigate the neutron shielding abilities of composites, inelastic, elastic, capture and transport numbers, total macroscopic cross section and mean free path parameters were determined with the help of GEANT4 simulation code. In addition, the number of transmitted neutrons at different sample thicknesses and neutron energies were also determined. It was observed that gamma radiation shielding properties were improved due to the increasing amount of gadolinium (III) sulfate and neutron shielding properties were improved due to the increasing amount of polyacrylonitrile. While the composite coded P0Gd50 exhibits a better gamma radiation shielding ability than the others, the neutron shielding of the sample coded P50Gd0 is also more favorable than the others. Highlights: Ternary composites containing polyester, C3 H3 N and Gd2 (SO4 )3 were produced. Their gamma shielding capacities were determined by three different methods. Neutron shielding capacities were investigated with GEANT4. It was observed that gamma shielding properties improved with increasing Gd2 (SO4 )3 . It was observed that neutron shielding properties improved with increasing C3 H3 N.